ANTI MICROBIAL RESISTANCE- ISSUES & A SOLUTION - Tripathy, Tridibesh; Das, Shankar; Singh, Dharmendra Pratap; Dwivedi, Rakesh; Mishra, Anjali (International Journal of Research -GRANTHAALAYAH, 2025)
The current article looks into the aspects of Anti Microbial Resistance (AMR) keeping in context of unjustified use of antibiotics during COVID 19. Gradually, it delves into the subject of scientific aspects related to antibiotic resistance. After discussing the process, it focuses on challenges ahead & suggests a solution through integration of Homoeopathy at large scale. As development of novel antibiotics is a time taking process, the therapeutic system of Homoeopathy can chip in with its ‘Isopathic’ remedies. To add to it, the Essential Medicine properties of Homoeopathy can only catalyze the process of integration for masses at large scale. It is only befitting for a country like India which has a huge population.